Subcutaneous aspergillosis with coexisting atypical mycobacterial infection - Duraipandian Jeyakumari; Rengasamy Gopal; Madasamy Balamurugan; Kulanthaivelu AmbedkarRaj; Subramanian Girija (Wolters Kluwer Medknow Publications, 2010)
A 60-year-old woman, a known diabetic and asthmatic, was admitted for acute exacerbation of chronic obstructive pulmonary disease. Physical examination revealed two soft nodules in the left infra axillary region. Fine needle aspiration cytology (FNAC) showed fungal granulomatous reaction suggestive of fungal infection. Periodic acid Schiff stain (PAS stain) revealed PAS positive, acutely branching, septate fungal hyphae. Wet mount of the aspirate revealed plenty of pus cells and branching septate hyphae. Ziehl-Neelsen (ZN) stain showed moderate numbers of acid fast bacilli. Culture yielded Aspergillus flavus and Mycobacterium fortuitum.